Wysokie krzyże iryjskie a grobowce Edessy - Bulas, Ryszarda M. (Vox Patrum, 2010)
The author in the article refers to a broad discussion on the origin of ideas and artistic inspiration for Celtic crosses. She refers to a Hilary Richardson of the Armenian and Georgian origin of the concept of the Celtic cross, also to the results of her book The symbols of pagan Celtic crosses. Myths, symbols, images. In this book she indicates a cultural affinity of Ireland and the Syria. She points to the compositional and iconographic parallels between the Early Medieval Irish crosses and tombs mosaics of Edessa, dated to the III century. Reinforcing the thesis of H. Richardson, indicates the possibility of the existence an artistic tradition, in Late Antiquity and Early Medieval Syria, which is able to reach Ireland. She indicates the Celtic crosses, which have the most parallels with Syrian decoration (monasteries from Arboe, Monasterboice, Kells, Clones). The author concludes that they are grouped only in the Middle East of Ireland, in several counties (Louth, Meath, Monaghan, Tyron).